Ultrasonographic manifestations of a rare granular cell tumor of the accessory breast: A case report. Issue 1 (January 2018) - Liu, Haotian; Tao, Meiying; Ding, Hongyu; Zhang, Peipei
Abstract: Rationale: The ultrasound manifestations of granular cell tumor (GCT) is a consequence of the histopathological characteristic of the tumor and can be distinguished from breast cancer. Patient concerns: A GCT is a rare, benign, hyperplasia-based lesion. Approximately 1% to 2% of GCTs are malignant. About 5% to15% of the cases occur in the breast, and it is relatively rare in the axillary accessory breast. There are no effective preventive measures for GCTs, early detection combined with a thorough and wide complete resection of the tumor remains the best treatment for a favorable outcome. Diagnoses: A 45-year-old female patient with an axillary mass of more than 3 months duration was examined through physical examination, color Doppler ultrasound and postoperative pathology. Interventions: A provisional diagnosis of left axillary lymph node enlargement was made and necessary investigations were advised. Outcomes: A differential diagnosis of accessory breast in the left arm pit, possibly malignant, or a solid mass in the left arm pit secondary to chronic inflammation. Postoperative pathology: GCT of axillary accessory breast, with tumor-free margins. Immunohistochemical staining showed strong S-100 positivity, CD68 positivity, and negative periodic acid-Schiff staining. Lessons: The ultrasound examination can detect GCT mass in the breast/accessory breast and is not easy to misdiagnosis.